Environmental aspects of oil and gas production - Robertson, John O.; Chilingar, George V., 1929- (John Wiley & Sons ; Scrivener Publishing, 2017)
Oil and gas still power the bulk of our world, from automobiles and the power plants that supply electricity to our homes and businesses, to jet fuel, plastics, and many other products that enrich our lives. With the relatively recent development of hydraulic fracturing ("fracking"), multilateral, directional, and underbalanced drilling, and enhanced oil recovery, oil and gas production is more important and efficient than ever before. Along with these advancements, as with any new engineering process or technology, come challenges, many of them environmental. More than just a text that outlines the environmental challenges of oil and gas production that have always been there, such as gas migration and corrosion, this groundbreaking new volume takes on the most up-to-date processes and technologies involved in this field. Filled with dozens of case studies and examples, the authors, two of the most well-known and respected petroleum engineers in the world, have outlined all of the major environmental aspects of oil and gas production and how to navigate them, achieving a more efficient, effective, and profitable operation. This groundbreaking volume is a must-have for any petroleum engineer working in the field, and for students and faculty in petroleum engineering departments worldwide.